The Impact of the Question and Answer Method on Students' Comprehension of the Akidah Akhlak Lessons at MI Miftahul Ulum - Septantiningtyas, Niken; Umi Zakiyah, Zulfa; Fajri, Zaenol (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to compare how well the lecture approach and question and answer format improve student understanding. Methodology: This study uses a quasi-experimental design and a quantitative methodology. Thirty students make up the sample, which is split into two groups: 15 students in the experimental group, which employs the question-and-answer format, and 15 students in the control group, which operates the lecture format. Pretests and posttests were used to gather data, and paired and independent t-tests were used for analysis. Main Findings: The statistical analysis is validated by the findings of the homogeneity test, which indicate that the variance of the two groups is equal (p = 0.17). According to the results, students' comprehension is improved more by the question-and-answer format than by the lecture format. With a statistically significant difference (p = 2.1 × 10⁻⁶), the experimental group's posttest score (86.53) was higher than the control group's (68.8). Constructivist philosophy, which emphasises the value of interaction in creating knowledge, is consistent with these findings. Novelty/Originality of this study: According to the study, using a question-and-answer format greatly improves pupil comprehension. According to the practical implications, teachers should implement this approach to boost student involvement in Akidah Akhlak learning. Future studies can examine integrating the question-and-answer method with other instructional techniques for the best results.